2006
DOI: 10.1364/ol.31.001414
|View full text |Cite
|
Sign up to set email alerts
|

Two-step phase-shifting interferometry and its application in image encryption

Abstract: Conventional phase-shifting interferometry (PSI) needs at least three interferograms. A novel algorithm of two-step PSI, with an arbitrary known phase step, by which a complex object field can be reconstructed with only two interferograms is proposed. This algorithm is then applied to an information security system based on double random-phase encoding in the Fresnel domain. The feasibility of this method and its robustness against occlusion and additional noise attacks are verified by computer simulations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
150
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(153 citation statements)
references
References 21 publications
0
150
0
1
Order By: Relevance
“…Collecting real and imaginary parts in (6) dictates that simultaneously γ = (1 + ατ 2r ) and γ = −jατ 2i thus leading to α = −1/τ 2 and hence…”
Section: General Formulation Of Two Step Psh (A2h)mentioning
confidence: 99%
See 1 more Smart Citation
“…Collecting real and imaginary parts in (6) dictates that simultaneously γ = (1 + ατ 2r ) and γ = −jατ 2i thus leading to α = −1/τ 2 and hence…”
Section: General Formulation Of Two Step Psh (A2h)mentioning
confidence: 99%
“…It is shown that when the reference wave is sufficiently strong a condition C is met [6], and then only two holograms are required (C2H). However, in this case an entire scan of the AUT near-field intensity is needed to determine the minimum reference level.…”
Section: Introductionmentioning
confidence: 99%
“…Especially since the double random-phase encryption method [1] was proposed, all kinds of random-phase encoding (RPE) schemes based on diffraction or interference principles have been booming [2][3][4][5][6][7][8][9][10][11][12][13]. As the accompanying complementary opposites, the corresponding security analyses have also been carried out and have promoted the further development of optical encryption techniques [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…They can be categorized into the multi-and single-frame methods. As the multi-frame method, the phase shifting [5][6][7][8][9][10] and the simultaneous multiple detection method [11,12] were researched. For the single-frame method, the BM scan [13] (B-scan: lateral scan, M-scan: reference mirror scan), the B-scan-based Hilbert transform reconstruction [14], and the phase shift between two A-lines [15] methods have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…However, it requires several interferograms at the same location to build a single complex A-line, which is time consuming; the two-step phase-shifting method has been adopted particularly because it demands just two interferograms [6,7,9,10]. By utilizing multiple spectrometers [11] or a 3 × 3 coupler [12] for parallel detections, two interferograms of a phase difference could be simultaneously captured.…”
Section: Introductionmentioning
confidence: 99%